Changes In Oxygen Carrying Capacity Of Blood In Fish, Channa Punctatus (Bloch) Exposed To Chlorpyrifos - FIRDOUS AHMED MALLA, (International Journal of Pharma and Bio Sciences, 2012)
Organophosphate pesticides widely used all over the world to control pest. They ultimately make their way into aquatic habitat and proved harmful to fishes and other aquatic flora and fauna. Organophosphate insecticides that kills insects by disrupting their nervous system and is effective against a wide range of plant eating insects. In the present study effect of sub lethal concentration of chlorpyrifos on oxygen carrying capacity of blood in fish, Channa punctatus (Bloch.). The study showed a significant decrease in the oxygen carrying capacity of blood after 24hrs. 48hrs.,72hrs. and 96hrs. respectively, when compared to control group